2020
DOI: 10.3390/ijerph17041162
|View full text |Cite
|
Sign up to set email alerts
|

How Does Paradoxical Leadership Affect Employees’ Voice Behaviors in Workplace? A Leader-Member Exchange Perspective

Abstract: We theorized and tested a leader-member perspective beyond the existing studies in paradoxical leadership and employee voice behavior. We proposed that paradoxical leadership influences employees’ voice behavior through psychological safety and self-efficacy. We also theorized that team size influences an extent to which the subordinates internalize their self-efficacy and psychological safety to exhibit proactive behavior. In a longitudinal study conducted on 155 subordinates and 96 supervisors in China, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 93 publications
4
38
0
Order By: Relevance
“…First, we contribute to the literature on paradoxical leadership by taking an actor-centric perspective and focusing on the intrapersonal consequences of paradoxical leaders and their own task performance. While previous studies have established that paradoxical leadership has an impact on followers [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ], the impact on leaders who engage in paradoxical leadership behaviors has been largely overlooked since working through paradoxes is an effortful, multi-stepped process [ 46 ]. Behaving paradoxically may tax leaders’ cognitive resources, which can result in psychological stress for leaders, and therefore, possibly influence their attitudes and behaviors [ 1 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, we contribute to the literature on paradoxical leadership by taking an actor-centric perspective and focusing on the intrapersonal consequences of paradoxical leaders and their own task performance. While previous studies have established that paradoxical leadership has an impact on followers [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ], the impact on leaders who engage in paradoxical leadership behaviors has been largely overlooked since working through paradoxes is an effortful, multi-stepped process [ 46 ]. Behaving paradoxically may tax leaders’ cognitive resources, which can result in psychological stress for leaders, and therefore, possibly influence their attitudes and behaviors [ 1 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxical leadership refers to leaders who simultaneously use two mutually opposing, interdependent, and complementary behaviors to satisfy both structural and individual needs [ 1 ]. This type of leadership is the most effective when leaders deal with organizational paradoxes related to balancing short- and long-term goals [ 2 ]. Emphasizing the coexistence of mutually independent elements, paradoxical leadership is a process that is based on personal characteristics and cognition, using a “both-and” strategy instead of an “either-or” strategy to resolve organizational paradoxes [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaders' communication is the basic behavior that strongly influences the subordinates at the workplace because the words leaders use for their workers directly affect performance (Xue et al, 2020). According to Sullivan (1988).…”
Section: Leader's Motivational Language and Employee Innovative Work ...mentioning
confidence: 99%
“…Research involving team voice only takes team characteristics as antecedent variables [ 18 , 19 ], without the influence of the thinking style of leaders on team voice behavior [ 8 ]. Previous studies have found that paradoxical thinking of leaders can improve team competitive advantage [ 20 ] and the good development of employees [ 21 ] and voice behavior [ 17 , 22 ]. However, the research of leadership paradoxical thinking on voice behavior at the team level is still relatively lacking.…”
Section: Introductionmentioning
confidence: 99%